Brazil's Literatura de Cordel: The Poetry of the People - Luyten, Joseph (Kasarinlan: Philippine Journal of Third World Studies; Vol 2 No 1 (1986), 2007)
Brazil, similar to most Third World countries, has a huge percentage of its population as illiterate. Although considered ignorant by the elites, these people have their own systems of communicating. The most important of these is the so-called Literatura de Cordel. This refers to a popular printing of narrative poems which are made to be sung or read aloud. This paper argues that for Brazilian, and other Third World people’s behavior to be better understood, it is important to know how the common people comprehend the world and communicate among themselves. Moreover, in order to have a better knowledge of Western literature and culture, it is necessary to know the origin and formation of their systems of communication. Thus, this paper discusses the nuances in Brazilian literature, emphasizing the so-called poetry of the people; and goes beyond it by discussing the popular literature of other regions such as Africa, Europe and America.
Keywords: Brazil, system of communication, Third World, Literatura de Cordel, popular literature, culture